High-resolution Chest CT Features and Clinical Characteristics of Patients Infected with COVID-19 in Jiangsu, China. (June 2020) - Dai, Hui; Zhang, Xin; Xia, Jianguo; Zhang, Tao; Shang, Yalei; Huang, Renjun; Liu, Rongrong; Wang, Dan; Li, Min; Wu, Jinping; Xu, Qiuzhen; Li, Yonggang
Highlights: An outbreak of pneumonia of COVID-19 was recently reported in China, with highly infectious. This was a multi-centered study included 234 inpatients confirmed with COVID-19 from 13 hospitals during 17 days (from January 10th to February 7th 2020) in Jiangsu province. Most of these cases were introduced from Wuhan, and they might have some distinctive clinical and imaging features. The comprehensive chest CT characteristics and clinical features of patients with COVID-19 were described in this study. Abstract: Background: A pneumonia associated with the coronavirus disease 2019 (COVID-19) recently emerged in China. It was recognized as a global health hazard. Methods: 234 inpatients with COVID-19 were included. Detailed clinical data, chest HRCT basic performances and certain signs were recorded Ground-glass opacity (GGO), consolidation, fibrosis and air trapping were quantified. Both clinical types and CT stages were evaluated. Results: Most patients (approximately 90%) were classified as common type and with epidemiologic history. Fever and cough were main symptoms. Chest CT showed abnormal attenuation in bilateral multiple lung lobes, distributed in the lower and/or periphery of the lungs (94.98%), with multiple shapes. GGO and vascular enhancement sign were most frequent seen, followed by interlobular septal thickening and air bronchus sign as well as consolidation, fibrosis and air trapping. There were significant differences in most of CT signs between different stage groups. The SpO2 and OI were decreased in stage IV, and the CT score of consolidation, fibrosis and air trapping was significantly lower in stage I ( P < 0.05). A weak relevance was between the fibrosis score and the value of PaO2 and SpO2 ( P < 0.05). Conclusions: Clinical performances of patients with COVID-19, mostly with epidemiologic history and typical symptoms, were critical valuable in the diagnosis of the COVID-19. While chest HRCT provided the distribution, shape, attenuation and extent of lung lesions, as well as some typical CT signs of COVID-19 pneumonia.